Educandy assisted as learning media to improve critical thinking skills on light material in elementary school - Aditya Rizqi Putra Purnomo; Zulherman Zulherman (Himpunan Pengembang Kurikulum Indonesia, 2025)
The low critical thinking skills of students in science education serve as the primary background for this study. Therefore, this research and development aims to produce and test the effectiveness of an Edu-Game-based learning medium on the Educandy platform for the topic of Light in 5th-grade elementary school. This study employed the RnD method using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research involved media and material experts for feasibility testing, as well as 5th-grade students from three different elementary schools. The validation results from the experts indicated a feasibility rating of